The Impacts of Social Media Influencer Marketing on Body Dysmorphic Disorder Among the Generation Z - Kadavathe Peedikayil, Siddique (Tecno Scientifica Publishing, 2025)
The increased time spent on social media and other digital environments has significantly impacted people’s lives, health, and social interactions. Social media influencers often lead adolescents to focus excessively on perceived beauty ideals and appearance flaws, as they tend to compare their self-image with what they see on social media platforms. This behavior may contribute to the development of body dysmorphic disorder (BDD). This research aims to investigate the effects of influencer marketing on BDD among Generation Z and to examine the extent to which they feel pressured to conform to unattainable and unrealistic beauty standards. A review of peer-reviewed articles was conducted using MedLine, PubMed, and Emerald, following the methodology of a systematic literature review. Articles retrieved in the initial search were screened using inclusion and exclusion criteria based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After applying the CASP tool, six articles were selected for final review. A narrative analysis was conducted to examine the data regarding the impact of social media influencer marketing on BDD. Findings suggest that social media advertisements and influencer marketing lead adolescents to feel dissatisfied with their body image and to negatively assess their physical appearance. They are especially vulnerable to developing BDD, showing symptoms such as frequent mirror checking, exercise obsession, and constant comparison of their bodies with others. This study recommends that adolescents enhance their critical thinking skills and develop greater awareness of social media and influencer marketing content to help prevent the onset of BDD.